Novel CA-125 antigen determination in serum by electrochemical methods with onion oil-containing organo-hydrogels - Duygu Alpaslan; Hilal Demir Kıvrak; Tuba Erşen Dudu; Ömer Er (MANAS: Journal of Engineering)
CA-125 antigen is a glycoprotein that can be found at distinct levels in blood samples according to the phases of ovarian cancer. Herein, we designed novel onion oil-organo-hydrogels (OOHGs) to detect CA-125 antigen at high sensitivity and selectively via electrochemical methods. OOHGs produced are characterized by swelling analysis and Fourier Transform Infrared Spectroscopy (FT-IR). Cyclic voltammetry (CV), Electro impedance spectroscopy (EIS), and Differential pulse voltammetry (DPV) techniques in the potentiostat triple electron system are used for performing the electrochemical measurements. Performances and electron transfer resistances of OOHGs and OOHG+CA-125s are researched via CV and EIS, and the sensitivity properties such as LOD and LOQ of the sensor are determined via DPV. OOHG-2 among OOHGs produced exhibited the highest performance with 0.8151 mA/cm2 (815.1 A/cm2) value at determining CA-125 in serum medium. Moreover, this electrode is found that exhibit a wide linear range like a 1-500 ng/mL concentration range. The limit of quantification (LOQ) and the lowest of detection (LOD) for the OOHG-2 electrode are calculated as 0.531 U/mL and 0.265 U/mL (S/N=3), respectively. Further, the CA-125 antigen of the OOHG-2 electrode in interference results is observed that can be detected with high selectivity. With these results, it can be noted that the OOHG-2 electrode holds great hope for detection ovarian cancer by electrochemical methods.